2006
DOI: 10.2136/sssaj2005.0352
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and Carbon Sequestration of Afforested Pastures in Reclaimed Minesoils of Ohio

Abstract: Land‐use change affects many soil properties, including soil organic carbon (SOC) pool, and the transfer of atmospheric CO2 to terrestrial landscapes. The objective of this study was to evaluate the effects of converting pastureland to Australian pine (Casuarina spp) and Black locust (Robinia pseudoacacia L) forest on selected soil physical and chemical properties and SOC sequestration in reclaimed minesoils (RMS) of southeastern Ohio. The study sites were surface mined for coal, reclaimed and managed as pastu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 46 publications
2
74
3
2
Order By: Relevance
“…The RMSs could potentially act as a sink for atmospheric CO 2 [17,19,20,22,24]. Data from this study indicated that the RMSs under pasture accumulated SOC at higher rates than those under arable land use.…”
Section: Soil Organic Carbon and Nitrogen Poolsmentioning
confidence: 74%
See 1 more Smart Citation
“…The RMSs could potentially act as a sink for atmospheric CO 2 [17,19,20,22,24]. Data from this study indicated that the RMSs under pasture accumulated SOC at higher rates than those under arable land use.…”
Section: Soil Organic Carbon and Nitrogen Poolsmentioning
confidence: 74%
“…These assessments have documented rapid SOC accumulation with sequestration rates generally higher than in agricultural lands [15,17,20,22,23]. For example, Akala and Lal [15] reported C sequestration rates of 2 to 3 Mg·ha -1 ·yr -1 in the first 20 yrs after reclamation, decreasing to 0.4 to 0.7 Mg·ha -1 ·yr -1 by 20 to 30 yrs after reclamation.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies (Vitousek & Walker 1989, Pereira et al 2011, Fterich et al 2014, our findings confirm that the nitrogen-fixing black locust tree may contribute to the soil Cmic and Nmic pools, improving the rates of carbon and nitrogen cycling and their availability. Moreover, previous studies reported that black locust could be largely ameliorative by promoting the amount and availability of N in the soil (Tateno et al 2007, Qiu et al 2010, Yüksek 2012, improving the quality and structure of soil, and increasing root biomass and soil organic C sequestration (Ussiri et al 2006, Yüksek 2012, thus ameliorating the biological properties of soils , Wang et al 2012. Furthermore, some authors argued that the microbial dynamic pool is attached to the organic residues that supply available C and nitrogen contents in the soil (Wardle 1992, Araujo et al 2010.…”
Section: Soil Characteristicsmentioning
confidence: 99%
“…These types of mine soils were highly weathered, contained no or little acid-producing minerals, and often have normal pH values. Ussiri et al (2006) reported the pH values of top soils from Ohio reclaimed mining sites (13-28 years old, respectively) ranged from 6.9~8.1 under different vegetation. Besides, the good chemical quality of the original top soils was also reflected in the relative good performance of the lettuce seed in soil A solution.…”
Section: Lettuce Seed Germination Testmentioning
confidence: 99%